2018
DOI: 10.5539/gjhs.v11n1p63
|View full text |Cite
|
Sign up to set email alerts
|

Body Composition in Iraqi Women With Systemic Lupus Erythematosus

Abstract: BACKGROUND & OBJECTIVE: SLE is one of systemic diseases, targeting young patients, so we try to study the one of factors that affected these patients. The aim of our study is to describe the body composition in Iraqi lupus patients, and assess the effect of the disease activity, disease duration, treatment, and patients’ social class in development of sarcopenia. PATIENTS & METHOD: Sixty women, age > 18years with SLE and 56 matched controls were stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
4
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 9 publications
3
4
1
1
Order By: Relevance
“…Positive smokers made up 2.9 percent of SLE patients in the current investigation, which was similar to previous results [24], and no significant variations in BMI values were seen when compared to healthy people [25]. All of the subjects in this study had active disease, and the SLEDI value was 16.4, which was lower than the value reported by other researchers [24]. The majority of patients were treated with steroids and HCQ, with varying values for the other medicines, according to the current study, which was consistent with a previous report.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…Positive smokers made up 2.9 percent of SLE patients in the current investigation, which was similar to previous results [24], and no significant variations in BMI values were seen when compared to healthy people [25]. All of the subjects in this study had active disease, and the SLEDI value was 16.4, which was lower than the value reported by other researchers [24]. The majority of patients were treated with steroids and HCQ, with varying values for the other medicines, according to the current study, which was consistent with a previous report.…”
Section: Resultssupporting
confidence: 93%
“…The optimum cut off point of RPR was 0.0455, and the analysis of data showed that this cut off point had 79% sensitivity, 51% specificity 51%, 65% accuracy, 62% PPV 62%, and 70.6% NP (Table 6). Positive smokers made up 2.9 percent of SLE patients in the current investigation, which was similar to previous results [24], and no significant variations in BMI values were seen when compared to healthy people [25]. All of the subjects in this study had active disease, and the SLEDI value was 16.4, which was lower than the value reported by other researchers [24].…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…20 Another Iraqi study assessed body composition in Iraqi women with systemic lupus erythematosus revealed that there was no significant difference between body composition of lupus patients and controls. 21 Also, it has been reported that patients with spondyloarthritis and systemic sclerosis tend to have higher risk of sarcopenia than matched controls. 22 In systemic sclerosis, sarcopenic patients were found to have longer disease duration, worse lungs, and skin involvement.…”
Section: Discussionmentioning
confidence: 99%
“…By leading to reduced muscle power, resistance, and physical activity, the loss of muscle mass contributes to the restriction in functional independence and daily living activities [11]. Up to our knowledge, no previously reported study has examined the prevalence of sarcopenia in the Iraqi population, however, some studies estimated the prevalence of sarcopenia in certain diseases like systemic lupus erythematosus [12].…”
Section: Introductionmentioning
confidence: 99%